A hanseníase e a política de saúde em Uberlândia - Dorneles, Marcia Mattos (2005)
This present work aims to analyze the numbers of prevailing and detection of leprosy that make Minas Gerais an area of reproduction of this disease, in areas with notorious economic development such as Uberlandia. It was necessary to review the social construction and the stigmas created around leprosy with an historical perspective, as well as the social production and reproduction of it in Minas Gerais, specifically in Uberlandia, whilst as a public health issue, identifying the impasses and perspectives for the elimination of the disease. It was adopted the following methodological approach: data gathering from the Health Bureau of Uberlandia, Health Bureau of Minas Gerais, DATASUS database and OPS (Pan-American Health Organization); large research on documents related to the Policy of Extermination of Leprosy in Brasil/Minas Gerais/Uberlândia, as well as the history of leprosy, moving back to biblical references. For the consolidation of information in the local context (Uberlândia), interviews were made with the coordinator of the Leprosy Elimination Program of Uberlandia, with the Social Assistant of the Lagoinha neighborhood Basic Health Unit and people of the same neighborhood, always searching for the connection between space construction and the disease perception. The execution of the research provided the conviction that dealing with such a wide subject, which considers not only statistical features, but also people s life and public policies, cannot be delimited by easily manipulated concepts and definitions, when referring to privileged places nationally speaking, the state of Minas Gerais and the city of Uberlândia, where contradictions and poverty situations live with wide offer of good health-care services, if compared to the whole national context. This way, the contribution of this work consists on providing a moment of reflection about the socialspatial, historical and political questions that involve leprosy.